2021
DOI: 10.3390/brainsci11030345
|View full text |Cite
|
Sign up to set email alerts
|

Rat Locomotion Detection Based on Brain Functional Directed Connectivity from Implanted Electroencephalography Signals

Abstract: Previous findings have suggested that the cortex involved in walking control in freely locomotion rats. Moreover, the spectral characteristics of cortical activity showed significant differences in different walking conditions. However, whether brain connectivity presents a significant difference during rats walking under different behavior conditions has yet to be verified. Similarly, whether brain connectivity can be used in locomotion detection remains unknown. To address those concerns, we recorded locomot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 67 publications
0
3
0
Order By: Relevance
“…Some studies have shown that using raw EEG signals or whole-time functional network metrics as features can effectively detect the locomotion state of subjects [ 25 , 58 ]. Our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have shown that using raw EEG signals or whole-time functional network metrics as features can effectively detect the locomotion state of subjects [ 25 , 58 ]. Our results (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the size of each electrode point was used to indicate the number of connections the electrode point has. It was worth mentioning that the edge threshold of the network was set to 50% of the strongest connections (i.e., only keep edges that are more than 50% of the strongest connections) [ 25 ]. Finally, the BrainNet Viewer toolbox [ 26 ] was used to visualize the brain functional network.…”
Section: Methodsmentioning
confidence: 99%
“…Cats can also actively adjust their limbs to negotiate the obstacles on treadmill, and the motor cortex and posterior parietal cortex play an important role in this process [ 19 , 20 ]. A previous study on rodents has demonstrated that the motor cortex actively participates in the movement control of the hind limbs when rats walk freely on flat ground, a treadmill, or stairs [ 21 ] and the brain connectivity showed different changes when rats walk on slopes with different inclination angles [ 22 ]. In addition, the sensorimotor cortex of rats actively involved in the adjustment of gait during bipedal walking on a treadmill or stairs [ 23 ].…”
Section: Introductionmentioning
confidence: 99%